Wetting patterns and bacterial distributions in different soils from a surface point source applying effluents with varying Escherichia coli concentrations - Li, J. (2020)
Experiments were conducted to study the transport of a typical bacterium, Escherichia coli (E. coli), in a sandy and a sandy loam soil under different application rates and input concentrations. A 30° wedge-shaped plexiglass container was used to represent one twelfth of the complete cylinder in the experiments. The apparent cylindrical application rate varied from 1.05 to 5.76 L h−1 and the input concentration of E. coli from magnitude of 102 to 107 colony-forming unit (CFU) mL−1. For both soil types tested, an extremely high concentration of E. coli was observed in the proximity of the point source, and the peak value increased with an increased input concentration. In principle, using an emitter with relative lower application rate would be effective to restrict E. coli transport. To reduce bacterial concentration in the sewage effluent during wastewater treatment is important to decrease the risk of soil contamination caused by irrigation with sewage effluent.